Saving the news : why the Constitution calls for government action to preserve freedom of speech - Minow, Martha, 1954- (New York, NY : Oxford University Press, 2021)
Martha Minow takes stock of the new media landscape. She focuses on the extent to which our constitutional system is to blame for the current parlous state of affairs and on our government's responsibilities for alleviating the problem. She further outlines an array of necessary reforms, including a new fairness doctrine, regulating digital platforms as public utilities, using antitrust authority to regulate the media, policing fraud, and more robust funding of public media.
Also issued in print: 2021.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on June 7, 2021).
Keywords: Press law -- United States; Freedom of the press -- United States; Press -- United States; Law; Laws of specific jurisdictions & specific areas of law